2021
DOI: 10.1177/0363546520988151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cam Deformity on 3-Dimensional Computed Tomography With the Best-Fit Sphere Technique and the Alpha Angle Marking Method

Abstract: Background: Three-dimensional computed tomography (3D-CT) is commonly used for the evaluation of cam deformity; however, it does not display the cam border directly. Purpose: To compare the efficacy of the best-fit sphere (BFS) method and the alpha angle marking (AAM) method in 3D-CT evaluation for the cam border. Study Design: Cohort study (Diagnosis); Level of evidence, 3. Methods: Twenty-six cases of cam deformity, confirmed during hip arthroscopy, were included in this study. All patients underwent a CT sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…These results are comparable to the metrics of cam morphology obtained using alternative techniques. 12 , 25 , 28 Kang et al 28 used a BFS method to describe cam morphology in 5 patients and reported a mean deformity height ranging from 0.78 to 2.65 mm. In a series of 26 patients with cam deformity, Cong et al 12 used the BFS method to quantify cam surface area and cited a mean area of 329.75 ± 42.7 mm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are comparable to the metrics of cam morphology obtained using alternative techniques. 12 , 25 , 28 Kang et al 28 used a BFS method to describe cam morphology in 5 patients and reported a mean deformity height ranging from 0.78 to 2.65 mm. In a series of 26 patients with cam deformity, Cong et al 12 used the BFS method to quantify cam surface area and cited a mean area of 329.75 ± 42.7 mm.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 25 , 28 Kang et al 28 used a BFS method to describe cam morphology in 5 patients and reported a mean deformity height ranging from 0.78 to 2.65 mm. In a series of 26 patients with cam deformity, Cong et al 12 used the BFS method to quantify cam surface area and cited a mean area of 329.75 ± 42.7 mm. 2 Harris et al 25 used statistical shape modeling on CT-based 3D bone models between patients with FAIS and control participants to evaluate morphologic differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, patients with symptom for more than 6 months, failure of conservative therapy and positive finding of labral tear on MRI were considered to be the indications of surgery. The surgical treatment of FAI was femoroplasty and/or acetabuloplasty under hip arthroscopy, to correct the osteophyte of cam deformity and/or pincer deformity, as well as repair the torn labrum [ 2 ]. However, only surgeons with high arthroscopic experience could product the hip arthroscopy, due to the hip’s deep location, narrow joint space and high curvature of joint surface, which leading to a very limited arthroscopic view [ 3 ].…”
Section: Introductionmentioning
confidence: 99%